2021
DOI: 10.3390/jcm10204745
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Prediction Model for Inflammatory Bowel Disease Based on Laboratory Markers. Working Model in a Discovery Cohort Study

Abstract: Inflammatory bowel disease (IBD) is a chronic, incurable disease involving the gastrointestinal tract. It is characterized by complex, unclear pathogenesis, increased prevalence worldwide, and a wide spectrum of extraintestinal manifestations and comorbidities. Recognition of IBD remains challenging and delays in disease diagnosis still poses a significant clinical problem as it negatively impacts disease outcome. The main diagnostic tool in IBD continues to be invasive endoscopy. We aimed to create an IBD mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…That the algorithm was established on a tertiary care dataset only, is a potential limitation of this algorithm. In a recently published study, the authors established a machine learning prediction model based on 702 IBD patients and 315 healthy controls 25 . The best classifier based on 16 parameters (including age, haemoglobin, and faecal calprotectin) achieved a mean average precision of 91% for UC and 97% for MC but could not distinguish various types of colitis either.…”
Section: Discussionmentioning
confidence: 99%
“…That the algorithm was established on a tertiary care dataset only, is a potential limitation of this algorithm. In a recently published study, the authors established a machine learning prediction model based on 702 IBD patients and 315 healthy controls 25 . The best classifier based on 16 parameters (including age, haemoglobin, and faecal calprotectin) achieved a mean average precision of 91% for UC and 97% for MC but could not distinguish various types of colitis either.…”
Section: Discussionmentioning
confidence: 99%
“…Among the key factors identified from the induction phase ML model, are the variables BCRP and MADCAM1: the former being a well-established marker in IBD 27 and has been identified as an influential prediction in prior ML analyses 28,29 ; the latter being the ligand of lymphocyte migration which is thought to be a key disease process in IBD. Furthermore, the ML model demonstrated that adalimumab treatment contributed to remission at the end of induction.…”
Section: Articlementioning
confidence: 99%
“…Artificial intelligence (AI) describes a variety of digital applications where human tasks (e.g., decision trees) are performed computer-based ( 238 ). As a particular AI application, machine learning (ML) algorithms can be developed to predict data (e.g., disease, disease subclassification) or outcomes based on previously generated patient data ( 239 ). The availability of novel biomarkers in addition to established clinical, endoscopic, and histologic scoring systems lends itself to integrating all these variables (potentially together with the results of other diagnostics such as abdominal ultrasonography) into meaningful ML algorithms ( 240 ) for the diagnosis and subclassification of canine CIE or the prediction of individual outcomes.…”
Section: Emerging Concepts and Future Directionsmentioning
confidence: 99%